2020
DOI: 10.1111/aje.12737
|View full text |Cite
|
Sign up to set email alerts
|

Termite mound density and distribution patterns across three land‐use types in the Vhembe District of the Limpopo Province, South Africa

Abstract: This study investigated the effect of land-use on density and distribution patterns of termite mounds. A total area of 12 ha was investigated using four 1 ha plots from each of three land-use types (mango orchards, maize fields and communal rangelands). A total of 297 mounds from four termite species were recorded. Plotted GIS coordinates for each mound in ArcMap showed a random distribution pattern in all land-use types. The mean number of mounds per hectare was significantly higher (p < 0.001) in communal ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…(2015) and Netshifhefhe et al (2020), who also reported a similar distribution pattern, potentially indicating interspeci c competition as a driving factor. Besides, our results align with other studies that have examined spatial distribution of epigean nests, such as those conducted by Cunha (2011) and Bruschini (2006), both of which also found a random distribution pattern.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…(2015) and Netshifhefhe et al (2020), who also reported a similar distribution pattern, potentially indicating interspeci c competition as a driving factor. Besides, our results align with other studies that have examined spatial distribution of epigean nests, such as those conducted by Cunha (2011) and Bruschini (2006), both of which also found a random distribution pattern.…”
Section: Discussionmentioning
confidence: 79%
“…However, magnitude of these impacts is largely dependent on spatial distribution and termite mound structure, which in turn are in uenced by environmental characteristics such as altitude, temperature, precipitation, availability of food and nesting resources, intra-and inter-speci c relationships, degree of environmental disturbance (Eggleton et al 2002), termite species, landscapes, land use, and colony size and age (Netshifhefhe et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Together, these two findings could help to explain the variation in nest regularity across disparate ecosystems and insect species (Getzin et al, 2019; Levings & Traniello, 1981; Netshifhefhe et al, 2020) and suggest that the most regular patterns should emerge in species and systems where substrates are homogeneous over extensive areas and nests are large relative to foraging territories. This finding has implications for debates over the mechanistic bases of spotted, gapped and mounded vegetation patterns (Cramer & Midgley, 2015; Gabet et al, 2014; Getzin et al, 2015; Getzin et al, 2019; Juergens, 2015; Tarnita et al, 2017; Zangerlé et al, 2016).…”
Section: Discussionmentioning
confidence: 93%